Commentary: An updated agenda for the study of digital media use and adolescent development – future directions following Odgers & Jensen (2020). (16th February 2020) - Prinstein, Mitchell J.; Nesi, Jacqueline; Telzer, Eva H.
Abstract : Odgers and Jensen's (Annual research review: Adolescent mental health in the digital age: Facts, fears, and future directions, Wiley‐Blackwell, 2020) review compellingly suggests that a rapid increase in the number of hours adolescents now dedicate to digital media use over the past decade may not be associated with concomitant changes in the prevalence of adolescent mental health disorders. Yet, there are many unexplored questions that deserve attention to fully understand how adolescents' use of digital media has transformed social experiences and adolescent development. In this commentary, we offer an agenda for researchers interested in examining digital media use within a broader developmental psychopathology framework. Specifically, we discuss past theories and emerging findings suggesting both deleterious and beneficial effects of digital media use, a need for greater semantic clarity in the field, and a call for greater methodological precision to fully capture concurrent and prospective associations between digital media use and adjustment. In addition, we suggest that it may be fruitful to dedicate less research attention toward the number of hours that adolescents spend using technology, and more on what specific behaviors teens engage in online. Moreover, more work is needed to understand individual vulnerability or resiliency factors that may impact online experiences. We review opportunities for future work on digital media use that may integrate findings from developmental social neuroscience and also discuss a need to investigate how adolescents' online behavior may be affecting developmental competencies offline. Adolescents' use of digital media is rapidly changing, and this is an important, yet challenging topic that deserves attention from investigators who study adolescent adjustment. Abstract : Read the full article at doi: 10.1111/jcpp.13190